2018
DOI: 10.1021/acsmacrolett.7b00968
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Quantum Dots as Photocatalysts for Controlled Light-Mediated Radical Polymerization

Abstract: Light-mediated radical polymerization has benefited from the rapid development of photoredox catalysts and offers many exceptional advantages over traditional thermal polymerizations. Nevertheless, the majority of the work relies on molecular photoredox catalysts or expensive transition metals. We exploited the capability of semiconductor quantum dots (QD) as a new type of catalyst for the radical polymerization that can harness natural sunlight. Polymerizations of (meth)­acrylates, styrene, and construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 42 publications
0
67
0
Order By: Relevance
“…Meanwhile, it provides spatial and temporal control for macromolecular synthesis by using light as an external stimulus to regulate the activation–deactivation equilibrium . So far, in this field, great progress has been made in the groups led by Hawker and Fors, Matyjaszewski, Yagci, Miyake, Boyer, Qiao, Haddleton and Anastasaki, Johnson, Boydston, Egap, and many others . Various strategies have been proposed to address typical challenges including the development of metal‐free photopolymerization systems, oxygen‐tolerance, and conducting polymerization under visible and even near‐infrared lights ,…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it provides spatial and temporal control for macromolecular synthesis by using light as an external stimulus to regulate the activation–deactivation equilibrium . So far, in this field, great progress has been made in the groups led by Hawker and Fors, Matyjaszewski, Yagci, Miyake, Boyer, Qiao, Haddleton and Anastasaki, Johnson, Boydston, Egap, and many others . Various strategies have been proposed to address typical challenges including the development of metal‐free photopolymerization systems, oxygen‐tolerance, and conducting polymerization under visible and even near‐infrared lights ,…”
Section: Figurementioning
confidence: 99%
“…[2] Photo-regulated RDRP inherits the merits of traditional thermally initiated controlled/living radical polymerizations,a llowing the controlled synthesis of polymers with predictable molecular weight (MW), narrow MW distribution, and well-defined end-group functionality.Meanwhile,i tp rovides spatial and temporal control for macromolecular synthesis by using light as an external stimulus to regulate the activation-deactivation equilibrium. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. [17] Va rious strategies have been proposed to address typical challenges including the development of metal-free photopolymerization systems, [4a, 5a, 10a] oxygen-tolerance, [9] and conducting polymerization under visible and even near-infrared lights.…”
mentioning
confidence: 99%
“…[1] Recently,t he integration of photo-mediated synthesis with reversible-deactivation radical polymerization (RDRP), including nitroxide-mediated polymerization (NMP), atom-transfer radical polymerization (ATRP), and reversible addition-fragmentation chain-transfer (RAFT) polymerization, is as ignificant advancement in this field. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others.…”
Section: Heteroatom-doped Carbon Dots (Cds) As Ac Lass Of Metal-free mentioning
confidence: 99%
“…

Ak ey challenge of photoregulated living radical polymerization is developing efficient and robust photocatalysts.Now carbon dots (CDs) have been exploited for the first time as metal-free photocatalysts for visible-light-regulated reversible addition-fragmentation chain-transfer (RAFT) polymerization. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. PET-RAFT polymerization of various monomers with temporal control, narrowdispersity ( % 1.04), and chain-endfidelity was achieved.Besides,itwas demonstrated that the CD-catalyzed PET-RAFT polymerization was effectively performed under natural solar irradiation.

Inspired by the solar-driven biosynthesis of proteins with high chain end fidelity and sequence control, macromolecular research has been focused on the exploitation of light to regulate modern polymer synthesis for ab etter control over the polymerization process.

…”
mentioning
confidence: 99%
“…The previously developed polymerized photocatalysts always require metal complexes, such as fac-[Ir(ppy) 3 ], 26 Ru(bpy) 3 Cl 2 , 27 zinc porphyrins, 28,29 and semiconducting nanoparticles. 30 Despite the excellent catalytic properties, trace amounts of these photocatalysts remaining in the polymer matrix may cause decomposition of the nal polymer products or lethal contamination. 31,32 Therefore, Boyer et al developed some metal-free catalysts such as Eosin Y and halogenated xanthene dyes to avoid metal contamination.…”
Section: Introductionmentioning
confidence: 99%